An Analysis of Cooperative Principle Maxim in the Written and Spoken Mode of Communication between Teacher and Students during Online Learning - Rutmiarta Gultom (Universitas Islam Sultan Agung, 2022)
This study had analyzed the application of the Cooperative Principles maxim in the teacher and students’ interaction during online learning, either in the spoken or written mode of communication. Previous research argues that there are some differences in interaction through spoken and written modes of communication. This current research analyzed the differences between the application of Cooperative principles maxim in the spoken and written mode of communication, it is because most of the research about Cooperative principles maxim only analyzed the utterances in one mode of communication. Then, although there is research on the Cooperative Principle maxim in both modes of communication still not been found that compared the Cooperative Principle maxim in the context of teacher and student interaction in that two modes of communication. This current research employed the descriptive qualitative method. The vocational high school students become the participants of this study because there is a must for them to be fluent in English because of the need to work after they graduate. The researcher is the primary instrument. However, the researcher also used a secondary instrument to find results. The secondary tool is the table used by some previous research on analyzing the flouting and violating of the maxim. Further, the results show in the teacher and students' interaction through the spoken mode of communication, that the most maxim flouted by the teacher and students is the maxim of quantity. Then, the most maxim violated in the spoken mode of communication by the teacher is the maxim of quantity however, students violated the maxim of quality. In the written mode of communication, teachers flouted the maxim quantity and manner for the most, but students flouted the maxim of quality and manner. However, the researcher did not find the occurrence of a violation of the maxim in the written mode of communication.